Struktur Komunitas Plankton di Inlet dan Outlet Danau Rawa Pening - Hariyati, Riche -; Wiryani, Erry -; Astuti, Yunita Kus (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2009)
Rawa Pening is a natural lake that has 17 inlet (rivers thats lead water into lake) and one outlet Tuntang RiverInlet and outlet of Rawa Pening Lake have differences in physico-chemistry factor and covering of plant water.Plankton is one of organism that influenced by this condition.The aim of this research is to establish structure community of plankton in inlet and outlet Rawa PeningLake. Sample was taken from 7 inlet (the downstream of Segalok, Torong, Panjang, Galeh, Rengas, Kedungringisand intercourse of Parat, Legi and Muncul downstream). Sample of outlet taken from upstream of Rawa PeningLake, around of port and before bridge. Sample then analyzed by diversity index, similarity index, equaliy index,and total individu per liter. Seventy seven plankton were found in inlet and outlet Rawa Pening Lake. Sixty fivespecies are phytoplankton and contains of 22 species Chlorophyceae, 38 species Bacillaryophyceae, 2 speciesCyanophyceae, 2 species Euglenophyceae and one species of Chrysophyceae. 12 species are zooplankton andcontains of 10 species Rotifera also one species Sarcomastigophora and one species of Copepoda. Based on diversityindex, equality index, and total individu the community structure of plankton in inlet is relatively stabil than in outletRawa Pening Lake.The similarity index showed that the level of species similarity is low. This is indicated thatstructure community of plankton in inlet and outlet is different.